Impact assessment of the IGR graphite block uneven impregnation with uranium on thermal strength properties - Surayev, A.S.; Irkimbekov, R.A.; Kozhabayev, Z.B.; Vityuk, V.A. (Recent Contributions to Physics, 2022)
The paper presents the results of a numerical interdisciplinary analysis of the fuel element of a heat capacity type research pulsed reactor (IGR). The fuel element of the IGR reactor is a graphite block impregnated with a solution of uranyl dinitrate. During the operation of the reactor, graphite blocks can be heated to high temperatures in a short period of time, which, together with the uneven impregnation of the block with uranium, which is due to the technological process of its manufacture, leads to the appearance of internal structural stresses. The purpose of this work is to make numerical estimation of the magnitude of thermal stresses arising in a graphite block. To carry out such an assessment, two computational models of a graphite block were built. One model is designed to perform neutron-physical calculations using a verified model of the IGR reactor core and the MCNP code, the other is designed to perform thermal strength analysis in the ANSYS software package. Thermal strength analysis includes two stages of calculations – thermal and structural (strength). Both models developed in the way to have the most similar topology, since this directly affects the correct distribution of the energy release over the volume of the block when transferring the results of the neutron-physical calculation to the thermal model. The operation of a graphite block as part of the reactor core was simulated during a start-up lasting 4 s at a stationary power of 2 GW, followed by cooling down for 5 s. Numerical values and distribution diagrams of temperature and stresses arising in the volume of the block are obtained. The results of the analysis confirm the effect of the uneven impregnation of the graphite block of the IGR reactor with a solution of uranyl dinitrate on its thermal strength characteristics.